Protocol between the Government of the United Kingdom of Great Britain and Northern Ireland and the Government of the Republic of Mauritius to amend the Convention for the Avoidance of Double Taxation and the Prevention of Fiscal Evasion with respect to Taxes on Income and Capital Gains, signed at London on 11 February 1981, as amended by the Protocols signed at Port Louis on 23 October 1986, 27 March 2003 and 10 January 2011, Port Louis, 28 February 2018. ([2018-08-03]) - Unknown
No abstract available